2016
DOI: 10.1128/jvi.03010-15
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 Interacts with Influenza A Virus NS1 and NP Proteins and Exerts Antiviral Function through Regulation of Stress Granule Formation

Abstract: DDX3 belongs to the DEAD box RNA helicase family and is a multifunctional protein affecting the life cycle of a variety of viruses. However, its role in influenza virus infection is unknown. In this study, we explored the potential role of DDX3 in influenza virus life cycle and discovered that DDX3 is an antiviral protein. Since many host proteins affect virus life cycle by interacting with certain components of the viral machinery, we first verified whether DDX3 has any viral interaction partners. Immunopreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 64 publications
1
57
0
Order By: Relevance
“…demonstrated that DDX3 interacted with influenza virus NS1 and NP proteins, and localized to virus induced SGs (Thulasi Raman et al, 2016). Furthermore, that study indicated that DDX3 is capable of nucleating stress granule formation, and that the core helicase domain of DDX3 was sufficient for its localization to SGs (Thulasi Raman et al, 2016). This offers further support to the loss of interactions we observed between VEEV-nsP3 and the host translational machinery with treatment of RK-33.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…demonstrated that DDX3 interacted with influenza virus NS1 and NP proteins, and localized to virus induced SGs (Thulasi Raman et al, 2016). Furthermore, that study indicated that DDX3 is capable of nucleating stress granule formation, and that the core helicase domain of DDX3 was sufficient for its localization to SGs (Thulasi Raman et al, 2016). This offers further support to the loss of interactions we observed between VEEV-nsP3 and the host translational machinery with treatment of RK-33.…”
Section: Discussionsupporting
confidence: 66%
“…ND ¼ not detectable. demonstrated that DDX3 interacted with influenza virus NS1 and NP proteins, and localized to virus induced SGs (Thulasi Raman et al, 2016). Furthermore, that study indicated that DDX3 is capable of nucleating stress granule formation, and that the core helicase domain of DDX3 was sufficient for its localization to SGs (Thulasi Raman et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies have highlighted an important function of other viral RNA helicases such as DDX3, DDX21, and DDX60 in virus sensing (Fullam and Schroder, 2013; Miyashita et al, 2011; Thulasi Raman et al, 2016). DDX3 was shown to interact with influenza NS1 and NP prote ins and to act as an antiviral protein by regulating stress granule formation, whereas DDX21 was shown to inhibit viral RNA and protein synthesis during infection through sequential interactions with PB1 and NS1 (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stress granules are assembled during cellular stress conditions to store mRNA and ribonucleoproteins, and to stall translation initiation. Both of these structures participate in cellular response against viruses and restriction of viral replication [51,133]. Importantly, the fact that RLRs can also be recruited to and activated in stress granules further strengthens and interconnects the multiple roles of DDX3 in innate immunity [134].…”
Section: Ddx3mentioning
confidence: 90%